NILAI â€“ NILAI MORAL DALAM TIGA CERITA PENDEK KARYA SIR ARTHUR CONAN DOYLE - WAMBURYE, YULIANA MARISCA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Sir Arthur Conan Doyle was one of England prose writer in the genre of detective fiction. His fiction â€œconsulting detectiveâ€, Sherlock Holmes, was still famous around the globe until today. He wrote the total of 60 cases of Sherlockâ€Ÿs adventures. His works mainly published in Victorian era. The research entitled â€œNilai-Nilai Moral Dalam Tiga Cerita Pendek Karya Sir Arthur Conan Doyleâ€ aims to identify, classify and analyze the moral values through the characterâ€Ÿs dialogues and narratorâ€Ÿs narratives and the relevance of those moral values with the Victorian era morality. Â The data had been collected by focusing on the characterâ€Ÿs dialogues and narratorâ€Ÿs narratives as the elements of prose which reveal the moral values within the three short stories entitled A Scandal in Bohemia, A Case of Identity and The Five Orange Pips. In order to analyze the moral values within the three short stories, the writer uses theory of function of literature by Wellek and Warren (1949), which they derived from Horaceâ€Ÿs Dulce et Utile about the purposes of literature which are to educate and entertain the readers and to analyze the relevance, the writer uses the theory of literature and sociology also by Wellek and Warren (1956) about how a literary work should be able to represent the reality of life. The writer finds that there are three moral values contained in those three short stories, which are, mutual assistance, concern, and giving respect to others and as for the relevance, the writer finds that Victorian era people has six values and there are two relevance between the moral values found in the three short stories and those six values, which are the relevance between mutual assistance and concern with a sense of duty and responsible towards the less well of and between respect and how the people of Victorian era give respect to their others. Â Keywords: Moral Values, Victorian Era, Sir Arthur Conan Doyle